ANALISIS FRAMING PEMBERITAAN PEMECATAN PEGAWAI KPK PADA MEDIA ONLINE TEMPO.CO DAN KOMPAS.COM - Hilmi Hanstuka (2022)
Reports about Komisi Pemberantasan Korupsi (KPK) and issue of weakening the KPK institution always appear frquently in the mass media every year. News about corruption is considered important by the public. On September 30, 2021, 57 former KPK employees were fired because they did not pass Tes Wawasan Kebangsaan (TWK) as a condition for changing the status of KPK employees to ASN. This incident became a polemic until former KPK employees were inaugurated as ASN Polri on December 8, 2021. This study aims to find out how the construction of framing and the prominence of online media aspects of tempo.co and kompas.com in response to the polemic of dismissing KPK employees. The selection of news is focused on news about the dismissal of KPK employees and news about the recruitment of former KPK employees to become Polri ASNs. The selection of media is based on the size of the media and the differences in language style between the two media. This study uses the Entman framing method to determine the construction and highlighting aspects of each media. This research shows that Tempo show its side with former KPK employees and consistently emphasizes that the implementation of TWK is filled with various problems, one of which is human rights violations. Meanwhile, Kompas tends to be balanced by constructing that TWK is not legally wrong, but the implementation is a different matter. Kompas consistently emphasizes the recruitment of former KPK employees to become ASN Polri is a solution to the existing polemic.